Evaluation of the effect of phacoemulsification surgery on retinal and choroidal microvasculature in diabetic patients using optical coherence tomography angiography - S. Nazem Ibrahim; Mona K. Abdellatif; Alaa F. Mahmoud; Tamer F. Eliwa (Journal of the Egyptian Ophthalmological Society)
Aim To evaluate the effect of phacoemulsification surgery on retinal and choroidal microvasculature in diabetic patients using optical coherence tomography angiography (OCTA). Settings and design A prospective comparative case-control study was performed at the Ophthalmology Department of Ain Shams University hospital, between November 2020 and November 2022. Patients and material A total 50 eyes of 35 cataractous patients were included in this prospective study and divided into two groups: the control group (25 eyes of 19 patients) and the diabetic group (25 eyes of 16 patients with mild nonproliferative diabetic retinopathy). All patients underwent routine ophthalmic examination, OCT and OCTA scans of the macula before phacoemulsification surgery and 1 week, 1, 3, and 6 months after the surgery. Results The best corrected visual acuity significantly improved in both groups by ∼ 0.26 logMAR units in control and diabetic groups (P <0.001 for both). The mean change in central subfoveal thickness was 23.44±43.7 versus 13.6±22 um (P=0.3) in the control group and the diabetic group, respectively but statistically insignificant. There was insignificant change in each group in all vascular parameters during the follow-up period. In addition, there was insignificant difference between the two groups at each visit in most vascular parameters of superficial vessel density, deep vessel density (DVD), and choriocapillaris vessel density (CC VD). On the other hand, the diabetic groups have significantly lower superficial vessel density of whole image and perifovea at 1 week than controls (42.92±4.54% vs. 46.16±3.98%, P=0.01 in the whole image, respectively) (44.29±4.87% vs. 47.32±3.85%, P=0.018 in perifovea, respectively). The diabetic group also showed significantly higher parafoveal deep vessel density than the control group at 1 month postoperatively: 52.67±4.00 versus 47.24±9.85% (P=0.014) that leveled up on month 3 and 6 (P=0.397, 0.538, respectively). The diabetic group showed lower CC VD of the whole image than the control group at 1 week postoperatively: 70.60±2.87 versus 72.22±1.98%, respectively (P=0.025), and also significantly lower CC VD of perifovea than the control group at 1 week: 71.19±2.82 versus 72.72±2.20% (P=0.038), 1 month: 71.08±2.87 versus 72.78±2.61% (P=0.033) and 3 months: 71.35±2.63 versus 72.83±2.52% (P=0.048). Those values leveled up at the last postoperative visit at month 6 (P=0.152). Conclusion Phacoemulsification surgery may lead to the transient and mild reduction of choroidal blood flow in diabetic eyes rather than retinal blood flow. Most of choroidal and retinal vascular changes happened in the perifoveal area within 1 week to 1 month postoperatively and rarely extended to 3 months.